Analysis of Structural, Optical, and Aquaphobic Properties of Zirconium Oxide Nanofilms by Varying Sputtering Gas - Kumar Sujit; Dave Vikramaditya; K. Vetri Velmurugan; Yakkala Bhaskarrao; Rupali Singh; Bhasker Pant; Amit Kumar Sharma; Hari Kumar Singh; Lijalem Mulugeta (Advances in Materials Science and Engineering)
The problem of contamination in ceramic insulators was found to be frequent in power transmission lines and transformers. The key aim was to develop aquaphobic zirconium oxide (ZrO2) thin films using DC reactive magnetron sputtering over glass insulators to mitigate contamination problems. This was achieved by introducing O2 and Ar gas in the sputtering chamber, and three properties, namely, structural, optical, and aquaphobic, were inspected by changing the sputtering gas ratio (oxygen/argon). These properties were chosen based on comparison with the bulk ZrO2. These deposited ZrO2 samples were identified by X-ray diffractometer (XRD), atomic force microscopy (AFM), UV-Vis-NIR spectrophotometer, and contact angle goniometer (CAG). For all the samples, coatings were found to be limpid, clear, and aquaphobic. Coarseness (62.813 nm) and the contact angle made by water to the surface (107.45°) were found utmost as deposited at 0.25 oxygen/argon gas ratios. The transmittance and band gap were also found to be 90% and 5.33 eV, respectively, at this particular ratio.